The Situation of the Tsotsil Language from Chiapas, Mexico: Orality and Writing - Carpio, Karla Del (International Journal of Educational Studies, 2025)
This manuscript emphasizes the linguistic and cultural richness of Mexico as it is the country that has approximately 68 language groups. Mexico is considered one of the countries with the largest indigenous population in Latin America. The languages of these communities have been characterized by their orality. However, the speed with which many indigenous languages have disappeared globally shows the need to look for solutions that contribute to their revitalization and promotion. This article focuses on the indigenous Mayan Tsotsil language spoken in Chiapas, Mexico to give a concrete example of the reality of indigenous languages and the efforts of their speakers and various agents to ensure these languages are used, preserved, and promoted. Also, the manuscript stresses the importance of accompanying the orality of indigenous languages to a writing system to increase the possibilities of their use not only in the present but also in the future. It is emphasized that the writing of indigenous languages contributes to vindicating, valuing and strengthening the languages and cultures of indigenous peoples. In addition, the writing system of indigenous languages helps to expand the (informal and formal) domains in which these languages can be used and decreases the possibility for these languages to be replaced by Spanish. It also increases the prestige (of these languages) and the pride of their speakers. It is concluded that any attempt to maintain and foster the vitality of the linguistic and cultural diversity of indigenous peoples is worthwhile since the linguistic diversity is a basic principle that contributes to peace and safety by promoting collaboration among peoples through education, science and culture with the purpose of universal respect for justice, freedom and human rights.